2004
DOI: 10.1111/j.1365-2761.2004.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

The induction of laboratory‐based amoebic gill disease revisited

Abstract: Previous work in our laboratory defined a method of inducing laboratory-based amoebic gill disease (AGD) in Atlantic salmon, Salmo salar L. Gills of AGD-affected fish were scraped and the debris placed into fish-holding systems, eliciting AGD in naïve Atlantic salmon. While this method is consistently successful in inducing AGD, variability in the kinetics and severity of infections has been observed. It is believed that the infections are influenced by inherently variable viability of post-harvest amoeba trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 7 publications
0
76
0
Order By: Relevance
“…The gross gill scoring, histological scoring and in particular the molecular data presented showed that detection of N. perurans was possible within 2weeks post-infection and has been previously reported (Morrison et al, 2004;Taylor et al, 2007). Histological examination of the samples in this study identified pathological changes within the first week; however the observation of amoeba in the presence of pathology and therefore case definition was not confirmed by histology until the second week.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The gross gill scoring, histological scoring and in particular the molecular data presented showed that detection of N. perurans was possible within 2weeks post-infection and has been previously reported (Morrison et al, 2004;Taylor et al, 2007). Histological examination of the samples in this study identified pathological changes within the first week; however the observation of amoeba in the presence of pathology and therefore case definition was not confirmed by histology until the second week.…”
Section: Discussionmentioning
confidence: 46%
“…In order to conduct an infection trial for the comparison of the preferred assay with traditional screening methods, N. perurans was isolated from farmed Atlantic salmon affected by AGD in the west of Ireland using a method described in Downes et al (2015), adapted from Morrison et al (2004). The amoeba culture was established and maintained according to Crosbie et al (2012).…”
Section: Amoebae Culturementioning
confidence: 99%
“…Briefly, AGD had been maintained in this tank for several months, with introduced fish exhibiting gross signs of AGD within 3 d of cohabitation. The presence of Neoparamoeba pemaquidensis, the putative agent of AGD, was routinely confirmed using a modified indirect fluorescent antibody test (Roberts & Powell 2003b), PCR (Wong et al 2004), immunohistochemistry (Bridle et al 2003 and by visually identifying parasomes within isolated gill amoebae (Morrison et al 2004). All fish were fed to satiation daily with non-medicated pellets, and further lethally sampled 3 and 5 d into their cohabitation with AGD-affected fish.…”
Section: Methodsmentioning
confidence: 99%
“…Neoparamoeba sp. were harvested from the AGD affected Atlantic salmon held in the Aquaculture Centre, University of Tasmania, Launceston by a method described by Morrison et al (2004). In brief, infected gills were removed from AGD affected Atlantic salmon after euthanasia (anaesthetic overdose at 20 ml l -1 Aqui-S ® ).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Until now AGD infection has always been established by cohabiting naïve fish with infected fish (Howard et al 1993, Akhlaghi et al 1996, or by exposing fish to isolated, gill-associated Neoparamoeba sp. , Morrison et al 2004, Morrison et al 2005 as the disease cannot be reproduced using cultured organisms (Kent et al 1988, Howard et al 1993, Findlay et al 2000, Morrison et al 2005.…”
Section: Introductionmentioning
confidence: 99%